Premature ovarian insufficiency in young girls: repercussions on uterine volume and bone mineral density. (January 2015) - Bakhsh, Hanadi; Dei, Metella; Bucciantini, Sandra; Balzi, Daniela; Bruni, Vincenzina
Abstract Study objective: To evaluate biological differences among young subjects with premature ovarian insufficiency (POI) commencing at different stages of life. Design: Retrospective observational study. Setting: Careggi University Hospital Participants: One hundred sixty-two females aged between 15 and 29 years with premature ovarian insufficiency. Methods: Data were collected as a retrospective chart review of baseline evaluation at diagnosis of premature ovarian insufficiency (POI). About 162 participants were divided into four groups based on gynecological age. Two primary outcome variables (uterine development and bone mineral density (BMD)) were analyzed in terms of differences among groups and in a multivariate logistic regression analysis. Results: Uterine development was clearly jeopardized when estrogen insufficiency started at a very young age. Total body BMD showed significant differences among the four groups studied, clearly corresponding to the duration of ovarian function. Data were discussed in relation to the choice of hormone replacement therapy regimens.